Violin Education Kit (VOEDK) Alat Bantu Belajar Biola berbasis Aplikasi Android - Ridho, Ali; Rahmatullah, Fardhani Rozak; Setyawan, Harchanio Adi (Program Kreativitas Mahasiswa - Karsa Cipta, 2014)
In this student creativity competition karsa cipta division, we would like to create an application tool to learn violin instrument named Violin Education Kit (VOEDK), by using application on android to execute scoring process. The main goal of this tool is to help those who wanted to learn violin, especially for children. Also, it could help those who have not be able to read nots, because it has a basic music tutorial. The method uses an Arduino microcontroller to convert digital signal (Digital Signal Processing) from silent violin, then the converted digital signal would be transmitted to Android Tab by using bluetooth. The application on Android Tab would synchronised the digital signal with a certain note, then the result will appear like on a game fiture. This tool is also completed with sound effect and monitor sound, so hopefully user would not be bored in learning. Applicable for solo concert.Keywords: Android, Violin, Bluetooth, DSP..